Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Ex 9.3

Ex 9.3, 1
Important

Ex 9.3, 2

Ex 9.3, 3

Ex 9.3, 4 Important

Ex 9.3, 5

Ex 9.3, 6

Ex 9.3, 7 Important

Ex 9.3, 8

Ex 9.3, 9 Important

Ex 9.3, 10 Important

Ex 9.3, 11 Important You are here

Ex 9.3, 12

Ex 9.3, 13

Ex 9.3, 14

Ex 9.3, 15 Important

Ex 9.3, 16

Ex 9.3, 17 Important

Ex 9.3, 18

Ex 9.3, 19 Important

Ex 9.3, 20 Important

Ex 9.3, 21

Ex 9.3, 22 Important

Ex 9.3, 23 (MCQ)

Last updated at Aug. 11, 2023 by Teachoo

Ex 9.3, 11 Find a particular solution satisfying the given condition : (𝑥^3+𝑥^2+𝑥+1) 𝑑𝑦/𝑑𝑥=2𝑥^2+𝑥; 𝑦=1 when 𝑥=0(𝑥^3+𝑥^2+𝑥+1) 𝑑𝑦/𝑑𝑥=2𝑥^2+𝑥 𝒅𝒚 = (𝟐𝒙^𝟐 + 𝒙)/(𝒙^𝟑 + 𝒙^𝟐 + 𝒙 + 𝟏) 𝒅𝒙 Integrating both sides ∫1▒〖𝑑𝑦=∫1▒(2𝑥^2 + 𝑥)/(𝑥3 + 𝑥2 + 𝑥 + 1)〗 dx y = ∫1▒(𝟐𝒙^𝟐 + 𝒙)/( (𝒙 + 𝟏)(𝒙^𝟐 + 𝟏)) dx Rough x = −1 is a solution of x3 + x2 + x + 1 as (-1)2 + (-1)2 + (−1) + 1 = 0 Hence (x + 1) is one of its factors. So, we can write x3 + x2 + x + 1 = (x + 1) (x2 + 1) Integrating by partial fractions, using formula (𝟐𝒙^𝟐 +𝒙)/((𝒙 + 𝟏)(𝒙^𝟐+𝟏)) = 𝑨/(𝒙 + 𝟏)+(𝑩𝒙 + 𝑪)/(𝒙^𝟐 + 𝟏) (2𝑥^2 +𝑥)/((𝑥 + 1)(𝑥^2+1)) = (𝐴(𝑥^2+1) + (𝐵𝑥 + 𝑐)(𝑥 + 1))/((𝑥 + 1)(𝑥^2 + 1)) 2𝑥^2 + x = A (𝑥^2+ 1) + (Bx + C) (x + 1) Putting x = −1 2(−1)2 − 1 = A ((−1)2 + 1) + (B(−1) + C)(−1 + 1) 2 − 1 = A(2) + (–B + C)(0) 1 = 2A A = 𝟏/𝟐 Putting x = 0 0 = A (0 + 1) + (B(0) + C)(0 + 1) 0 = A + C(1) A = −C Since A = 𝟏/𝟐 ∴ C = (−𝟏)/𝟐 Putting x = 1 2(1) + 1 = A (12 + 1) + (B(1) + C) (1 + 1) 3 = 2A + 2B + 2C Putting A = 𝟏/𝟐, C = (−𝟏)/𝟐 3 = 2 × 1/2 + 2B + 2 (−1/2 ) 3 = 2B B = 𝟑/𝟐 Hence, (𝟐𝒙^𝟐 + 𝒙)/((𝒙 + 𝟏)(𝒙^𝟐+𝟏)) = 1/(2(𝑥 + 1)) + (3/2 𝑥 − 1/2)/(𝑥^2 + 1) = 𝟏/(𝟐(𝒙 + 𝟏)) + (𝟑𝒙 −𝟏)/(〖𝟐(𝒙〗^(𝟐 )+ 𝟏)) Now, our equation becomes y = ∫1▒〖(2𝑥^2 + 𝑥)/((𝑥 + 1)(𝑥^2 + 1)) 𝑑𝑥〗 y = ∫1▒〖𝟏/(𝟐(𝒙 + 𝟏))+𝟑𝒙/(𝟐(𝒙^(𝟐 )+𝟏)) − 𝟏/𝟐(𝒙^𝟐 + 𝟏) 𝒅𝒙〗 y = ∫1▒〖1/(2(𝑥 + 1)) 𝑑𝑥〗+∫1▒〖3𝑥/(2(𝑥^(2 )+1)) 𝑑𝑥〗−∫1▒〖 1/2(𝑥^2 + 1) 𝑑𝑥〗 y = 𝟏/𝟐 log (x + 1) +∫1▒〖𝟑𝒙/(𝟐(𝒙^(𝟐 )+𝟏)) 𝒅𝒙〗− 𝟏/𝟐 tan−1 x Integrating ∫1▒〖𝟑𝒙/(𝟐(𝒙^𝟐 + 𝟏)) 𝒅𝒙〗 Put t = x2 + 1 dt = 2x dx ∴ dx = 𝑑𝑡/2𝑥 So, ∫1▒〖𝟑𝒙/(𝟐(𝒙^𝟐 + 𝟏)) 𝒅𝒙〗 = 3/2 ∫1▒𝑥/𝑡×𝑑𝑡/2𝑥 = 3/4 ∫1▒𝑑𝑡/𝑡 = 𝟑/𝟒 log |𝒕|+𝒄 Putting back value of t ∫1▒〖3𝑥/(2(𝑥^2+1)) 𝑑𝑥〗 = 3/4 log (x2 + 1) + C Now, From (1) y = 1/2 log (x + 1) +∫1▒〖3𝑥/(2(𝑥^(2 )+1)) 𝑑𝑥〗− 1/2 tan−1 x y = 1/2 log (x + 1) +3/4 " log (x2 + 1)"− 1/2 tan−1 x + C Putting x = 0 and y = 1 1 = 1/2 log (0 + 1) + 3/4 log (0 + 1) − 1/2 tan−1 0 + C 1 = 1/2 log (1) + 3/4 log (1) − 1/2 tan−1 0 + C 1 = 0 + 0 − 0 + C 1 = C Putting value of C in (1) y = 𝟏/𝟐 log (x + 1) + 𝟑/𝟒 log (x2 + 1) − 𝟏/𝟐 tan−1 x + 1 y = 𝟐/4 log (x + 1) + 3/4 log (x2 + 1) − 1/2 tan−1 x + 1 y = 1/4 log (x + 1)2 + 1/4 log (x2 + 1)3 − 1/2 tan−1 x + 1 y = 1/4 [log〖 (𝑥+1)^2 〗+log〖(𝑥^2+1)^3 〗 ] "− " 1/2 " tan−1 x + 1 " As log 𝑎 + log b = log 𝑎b y = 𝟏/𝟒 𝒍𝒐𝒈〖〖 [(𝒙+𝟏)〗^𝟐 (𝒙^𝟐+𝟏)^𝟑] 〗 "− " 𝟏/𝟐 " tan−1 x + 1 "